Framing Analysis In Gender Perspective: On Media Online Mass News Of Sexual Harassment Cases In Tribunnews.Com And Detik.Com - Janah, Wardatul (Sean Institute, 2024)
Objective: This study aims to determine the differences in the framing of news of cases of sexual harassment on Tribunnews.com and Detik.com in the application of gender perspective journalism in the April 2018 period. Data Source: Primary data in this study are news texts in the form of news texts in the online media Tribunnews.com and Detik.com regarding news of sexual harassment cases during the April 2018 period. Secondary data in the form of notes or reports that have been arranged in archives or data has been collected by data collection agencies and published to the data user community or not published. Method: this method is a qualitative method using framing analysis theory from Pan and Kosicki. Results: The results of the framing analysis in this study are attached to the attachment table 3. Conclusion: Broadly speaking, the two media have different framing directives in packaging cases of sexual harassment, especially if viewed from the selection of diction. This certainly has an impact on the framing of news that can form a public opinion. The choice of certain words can indeed have an impact on the construction of the reality and meaning contained.